Música e vida: olhares sensíveis de jovens estudantes de instrumentos musicais - Pires, Jorge César de Araujo (Universidade Federal de São Carlos, 2022)
We believe it is possible to teach a musical instrument aimed at human formation, to make instrumentalists more critical, sensitive and amorous people aware of their human role in society. In this research, the learning of the musical instrument is understood as a social practice and music as a language and a form of artistic expression. As an educational process, learning a musical instrument can be a practice full of oppressive relationships, power disputes and colonialities. On the other hand, it can also be a coexistence with availability, with respect for learning, with understanding and appreciation of the other's knowledge, attitudes and worldviews. It can be an educational process inserted in social practices that consider each person as an active participant in the process, understanding the involvement of all subjects in the construction of knowledge. The aim of this study was to understand the perceptions of students about the human relationships that are established from the learning of musical instruments. The 6 research participants were, at the time of the study, aged between 15 and 17 years and lived in two different regions of our country: South and Southeast. We started from preliminary questions that later generated a research question. The first questions were: are these students interested in the general formation of the human being when learning a musical instrument? Are students, when looking for musical instrument classes, interested in other elements besides instrumental technique? How do students perceive interactions with teachers and the development of sensitivity, creativity, expression and affection? From these three questions, we arrived at a research question: What elements of human and musical development do students perceive when participating in the educational process of learning musical instruments? The qualitative research began in 2018 with theoretical studies, but data collection took place in the midst of the Covid 19 pandemic, in 2020. An online questionnaire was carried out as the first contact with the participants and later individual conversations were held and a virtual conversation circle. From the transcripts of the conversations, in the analysis of the data, two thematic units emerged: elements of human development and elements of musical development. From these elements, we can see the perceptions that the students participating in the research have of their learning as an instrumentalist and also as a human person. It was possible to perceive that the practice and learning of a musical instrument promoted the awareness of the students participating in the research on issues related to motivation, affection, relationship, sensitivity and subsistence. It was also possible to perceive how the practice and learning of a musical instrument is influenced and can influence the social context of those who practice it and their families.
Music and life: sensitive looks of young people students of musical instruments
Keywords: Aprendizagem de um instrumento musical; Educação Musical; Humanização; Learning a musical instrument; Music education; Humanization; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM